Assessment of Soil Contamination by Heavy Metals in the Al-Fatayeh Region, Derna, Libya - Mardhiyah Feraj,; Hamad Hasan, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study was conducted to assess the levels of contamination by certain heavy metals (Mn, Cr, Co, Ni, Cu, Pb) in soil samples collected at two depths (10 cm and 20 cm) from eight different sites in the Al-Fatayeh region, located east of Derna (Libya). The analysis focused on trace element concentrations expressed in parts per million (ppm) and was supplemented by comparisons with international environmental standards, including soil quality thresholds according to Dutch standards. The results showed that the majority of measured concentrations were below critical limits, except for copper at site seven, where a high value of 105.496 ppm was recorded at a depth of 10 cm, approaching the permissible limit (100 ppm). Manganese, chromium, cobalt, nickel, and lead were found to be significantly below environmental risk thresholds, suggesting moderate or natural pollution. Statistical analysis (ANOVA) revealed significant differences between depths and between sites for several elements, indicating spatial and vertical variability attributable to local pollution sources and soil physicochemical characteristics.